2011
DOI: 10.3389/fnins.2011.00135
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor NURR1 exerts concentration-dependent effects on target genes mediating distinct biological processes

Abstract: The transcription factor NURR1 plays a pivotal role in the development and maintenance of neurotransmitter phenotype in midbrain dopamine neurons. Conversely, decreased NURR1 expression is associated with a number of dopamine-related CNS disorders, including Parkinson’s disease and drug addiction. In order to better understand the nature of NURR1-responsive genes and their potential roles in dopamine neuron differentiation and survival, we used a human neural cellular background (SK-N-AS cells) in which to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 68 publications
0
51
0
Order By: Relevance
“…Nurr1 is a nuclear receptor transcription factor belonging to the NR4A family of orphan nuclear receptors and functions as a constitutively active transcription factor. Gene expression profiling of cells overexpressing Nurr1 has shown that miR-217 is a target of Nurr1 (28). The D 2 R interacts with Nurr1 via ERK signaling and is critical for its transcription (29).…”
Section: Discussionmentioning
confidence: 99%
“…Nurr1 is a nuclear receptor transcription factor belonging to the NR4A family of orphan nuclear receptors and functions as a constitutively active transcription factor. Gene expression profiling of cells overexpressing Nurr1 has shown that miR-217 is a target of Nurr1 (28). The D 2 R interacts with Nurr1 via ERK signaling and is critical for its transcription (29).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human neural SK-N-AS cells were conducted in which a number of stable clonal lines were constructed with graded NR4A2 gene expression to approximate levels of NR4A2 seen in dopaminergic neurons present in human substantia nigra [147]. Transcriptomic data acquired from these NR4A2-expressing clonal lines revealed that the effects of NR4A2 on target genes varied considerably as a function of its concentration.…”
Section: Nr4a2 In Cellular Homeostasis and Diseasementioning
confidence: 99%
“…The Nr4a genes are immediate-early genes transcribed rapidly in response to external stimuli (Peña de Ortiz & Jamieson, 1996). Mature NR4A proteins are capable of both positively and negatively regulating the transcription of their downstream targets (Johnson, Michelhaugh, Bouhamdan, Schmidt, & Bannon, 2011), which include plasticity-related genes such as Bdnf1 and Fosl2 (Hawk et al, 2012; Volpicelli et al, 2007). …”
Section: Introductionmentioning
confidence: 99%